Localized light chain amyloidosis: A self-limited plasmacytic B-cell lymphoproliferative disorder - Martínez, José C.; Lichtman, Eben I. (Frontiers in Oncology, 2022)
Immunoglobulin light chain amyloidosis can be either systemic or localized. Although these conditions share a similar name, they are strikingly different. Localized light chain amyloidosis has been challenging to characterize due to its lower incidence and highly heterogeneous clinical presentation. Here, we review the emerging literature, emphasizing recent reports on large cohorts of patients with localized amyloidosis, and provide insights into this condition’s pathology and natural history. We find that patients with localized amyloidosis have an excellent prognosis with overall survival similar to that of the general population. Furthermore, the risk of progression to systemic disease is low and likely represents initial mischaracterization as localized disease. Therefore, we argue for the incorporation of more sensitive techniques to rule out systemic disease at diagnosis. Despite increasing mechanistic understanding of this condition, much remains to be discovered regarding the cellular clonal evolution and the molecular processes that give rise to localized amyloid formation. While localized surgical resection of symptomatic disease is typically the treatment of choice, the presentation of this disease across the spectrum of plasmacytic B-cell lymphoproliferative disorders, and the frequent lack of an identifiable neoplastic clone, can make therapy selection a challenge in the uncommon situation that systemic chemotherapy is required.